How Dietary Habits and Nutritional Deficiencies Relate to Hyponatremia in Older Adults - Maaha Ayub; Meher Angez; Nabiha B. Musavi; Syed Tabish Rehman; Deepak Kataria; Rabeea Farhan; Namirah Jamshed (Journal of Ageing and Longevity)
Hyponatremia, a common electrolyte imbalance in older adults, results from physiological aging, medication use, and comorbidities, with significant implications for morbidity and quality of life. This narrative review aims to explore the impact of dietary habits and nutritional deficiencies on the development and management of hyponatremia in this population. A literature search identified relevant studies addressing the risk factors related to sodium balance, dietary intake, and nutrition. The key findings reveal that low sodium and age-related changes increase vulnerability to hyponatremia and its associated risks, including cognitive decline and falls. Nutritional strategies, such as optimizing sodium and protein intake and reducing processed food consumption, may offer preventative benefits. Future research should focus on tailored dietary interventions and establishing sodium intake guidelines specific to older adults. Implementing such strategies could improve the health outcomes and reduce the healthcare costs associated with hyponatremia in older populations.